File Security Design in Electronic Health Record (EHR) System with Triple DES Algorithm (3DES) at Jember Family Health Home Clinic - Yunus, Muhammad; Sakkinah, Intan Sulistyaningrum; Rahmawati, Ulfa Emi; Deharja, Atma; Santi, Maya Weka (International Journal of Health and Information System, 2023)
Electronic Health Record (EHR) is an electronic version of a patient's medical history maintained by a health care service from time to time. The hacking of medical record data by irresponsible parties is a security threat to the EHR system, including the EHR system belonging to the Jember Family Health Home Clinic which is not equipped with a file security system. This research was conducted by designing file security on the EHR system with the Triple DES (3DES) algorithm using UML (Unified Modeling Language) diagrams. The Triple DES (3DES) algorithm was chosen because it is considered secure in securing files. The results of this study are the design of adding file security with 3DES to the EHR system to help maintain the confidentiality of vital medical record data. Further research can be done by building a file security system using 3DES according to the design that has been made.